Production of Polyhydroxyalkanoates (PHA) for Biomedical Application using Sugar Industry Waste and Native Micro Flora via Biphasic System. - Paulraj, P; Periyavedi, S; Sajna, K; T Mohamed Javad, P; Sajeesh, P; Chandramohan, M; Ketharin, T (International Journal of Engineering and Technology, 2019)
Plastics are synthetic polymers that changed our daily life due to their applications. But itâ€™s increasing environmental problems had made the researchers find the alternative way such as usage of biodegradable plastics like Polyhydroxyalkanoates (PHA) which has similar properties to the conventional plastic. In this research production and characterization of PHAs using sugar industry wastes as a sole carbon source was carried in order to reduce the cost of production of PHA. Isolation of heterotrophic native micro flora from soil sample contaminated with sugar effluent for amylolytic and cellulolytic activity with PHA production potentials was carried out. Â Suitable conditions for PHA accumulation were optimized with 1X and 2X MSM with sugar effluent as a sole carbon source and bacteriostatic antibiotics as an inducer using bi-phasic system. A total of 14 different heterotrophic native bacterial strains were isolated, among them, 4 isolates showed starch hydrolytic property, 7 isolates showed cellulolytic activity and 7 were PHA producers. The strain with the highest PHA accumulation (99.99Âµg/mL of culture) in 2X MSM with sugar effluent within 6 hours was considered as a potential strain (53% of PHB CWD). The isolate was confirmed as Chryseobacterium Sp. using 16S rRNA sequencing.Â